2000
DOI: 10.4049/jimmunol.164.6.2964
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Histamine in the Cytokine Network in the Lung Through H2 and H3 Receptors: Stimulation of IL-10 Production

Abstract: Histamine, a well-known inflammatory mediator, has been implicated in various immunoregulatory effects that are poorly understood. Thus, we tested the hypothesis that histamine inhibits the release of a proinflammatory cytokine, namely TNF, by stimulating the release of an anti-inflammatory cytokine, IL-10. Alveolar macrophages (AMs) from humans, Sprague Dawley rats, and the AM cell line, NR8383, were treated with different concentrations of histamine (10−5-10−7 M) for 2 h prior to their stimulation with subop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 49 publications
3
81
0
Order By: Relevance
“…Moreover, in accordance with data obtained using monocytes/macrophages (18 -21), histamine does not induce TNF-␣ nor IL-12 production by DC. Histamine has been shown to induce IL-10 production by alveolar macrophages (22). In contrast, others reported that histamine alone did not induce IL-10 production by PBMC (18,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in accordance with data obtained using monocytes/macrophages (18 -21), histamine does not induce TNF-␣ nor IL-12 production by DC. Histamine has been shown to induce IL-10 production by alveolar macrophages (22). In contrast, others reported that histamine alone did not induce IL-10 production by PBMC (18,21).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effects of histamine, including inhibition of LPS-induced IL-12 and TNF-␣ production and upregulation of IL-10 production by PBMC, are mediated through H2 (19 -22); one report also involves H3 receptors in histamineinduced IL-10 production by macrophages (22). However, histamine has been shown to induce IL-6 and IL-8 production by endothelial cells through both H1 and H2 receptors (14,15).…”
Section: ϫ4mentioning
confidence: 99%
“…Human macrophages express all types of histamine receptors, H 1 , H 2 , and H 3 (24,25). Several studies have started to highlight the complexity of histamine's effects on cytokine network in human cells depending on the type of receptor activated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of IL-6 production generally occurs via H 1 receptors (54 -56), whereas inhibition of IL-1, TNF-␣, and IL-12 production by LPS-stimulated human monocytes is mediated by H 2 receptors (35,36,57). Furthermore, activation of H 2 and H 3 receptors stimulates IL-10 release from human monocytes and macrophages (11,25). These findings suggest that the local release of histamine in inflamed tissues may play a role in the modulation of the cytokine network more complex than originally thought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation